The therapeutic applicability of tyrosol and hydroxytyrosol for Dentistry (Research, Society and Development, 2020)
Tyrosol (2- (4-hydroxyphenyl) ethanol) and hydroxytyrosol (2- (3,4-dihydroxyphenyl) ethanol) are one of the major representatives of the phenolic compounds found in olives, olive oil and wine. They have high antioxidant, anti-inflammatory, antiviral and anti-tumor properties and are the target of several studies in the medical field. The aim of this work was to evaluate the results of tyrosol and hydroxytyrosol in the published literature with the intention of directing the information about the application of these phenolic compounds in the dental field. An integrative review of the literature published in the last 20 years was carried out, with the purpose of accessing the most recent evidence on the subject, without restriction on the language. It was concluded that, although there are few studies on the therapeutic application of tyrosol and hydroxytyrosol in dentistry, and many of them in vitro, the results shown the potential of these products for their application in dentistry. These compounds can be used in several clinical areas, mainly for anti-inflammatory, antioxidant and anti-tumor activities.